Cultural Heritage Under Siege : Laying the Foundation for a Legal and Political Framework to Protect Cultural Heritage at Risk in Zones of Armed Conflict - Weiss, Thomas G. (Thomas George), 1946-; Cuno, James B. (J. Paul Getty Trust occasional papers in cultural heritage policy, 2020)
The fourth volume of the J. Paul Getty Trust Occasional Papers in Cultural Heritage Policy series is the result of a multi-day discussion on the issue of cultural heritage under siege. It features an edited collection of papers and discussions by nineteen scholars and practitioners of different specialties in the field of cultural heritage. This paper, along with the other Occasional Papers, is free and downloadable online.